Outcomes of COVID-19 related hospitalisation among people with HIV in the ISARIC WHO Clinical Characterisation Protocol UK Protocol: prospective observational study - Geretti, AM; Stockdale, AJ; Kelly, SH; Cevik, M; Collins, S; Waters, L; Villa, G; Docherty, A; Harrison, EM; Turtle, L; Openshaw, P; Baillie, JK; et al. (Cold Spring Harbor Laboratory Press, 2020)
Background. There is conflicting evidence about how HIV infection influences COVID-19. We compared the presentation characteristics and outcomes of people with and without HIV hospitalised with COVID-19 at 207 centres across the United Kingdom. Methods. We analysed data from people with laboratory confirmed or highly likely COVID-19 enrolled into the ISARIC CCP-UK study. The primary endpoint was day-28 mortality after presentation. We used Kaplan-Meier methods and Cox regression to describe the association with HIV status after adjustment for sex, ethnicity, age, indeterminate/probable hospital acquisition of COVID-19 (definite hospital acquisition excluded), presentation date, and presence/absence of ten comorbidities. We additionally adjusted for disease severity at presentation as defined by hypoxia/oxygen therapy. Findings. Among 47,539 patients, 115 (0.24%) had confirmed HIV-positive status and 103/115 (89.6%) had a record of antiretroviral therapy. At presentation, relative to the HIV-negative group, HIV-positive people were younger (median 55 versus 74 years; p<0.001), had a higher prevalence of obesity and moderate/severe liver disease, higher lymphocyte counts and C-reactive protein, and more systemic symptoms. The cumulative incidence of day-28 mortality was 25.2% in the HIV-positive group versus 32.1% in the HIV-negative group (p=0.12); however, stratification for age revealed a higher mortality among HIV-positive people aged below 60 years. The effect of HIV-positive status was confirmed in adjusted analyses (adjusted hazard ratio [HR] 1.49, 95% confidence interval [CI] 0.99-2.25; p=0.06). Following additional adjustment for disease severity at presentation, mortality was higher in HIV-positive people (adjusted HR 1.63; 95% CI 1.07-2.48; p=0.02). In the HIV-positive group, mortality was more common among those who were slightly older and among people with obesity and diabetes with complications. Interpretation. HIV-positive status may be associated with an increased risk of day-28 mortality following a COVID-19 related hospitalisation.